Comprehensive dataset of shotgun metagenomes from oxygen stratified freshwater lakes and ponds - Moritz Buck (Nature Portfolio, 2021)
Measurement(s) Metagenome Technology Type(s) DNA sequencing Factor Type(s) lake Sample Characteristic - Environment lake with an anoxic hypolimnion • freshwater biome Sample Characteristic - Location Sweden • Finland • Canada • Switzerland • Commonwealth of Puerto Rico Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14191043